Symptoms of complex pelvic pain: A survey in three cohorts of women - Cecilie Therese Hagemann; Siri Spetalen; Susan Saga; Ingvild Bratlie; Vilde Dons; Signe Nilssen Stafne (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction There has been increased interest in addressing chronic pelvic pain and its complexity in women. The often multifactorial etiology of chronic pelvic pain and its heterogeneous presentation, however, make the condition challenging to manage. Overlap with other pain‐related conditions is frequently reported, and chronic pelvic pain may impact sexual function. Nevertheless, little is known about the symptom burden of chronic pelvic pain and more complex pelvic pain in different groups of women. Thus, the aim of our study was to use a newly validated Norwegian version of the Amsterdam Complex Pelvic Pain Symptom Scale (ACPPS) to describe and compare the symptom severity of complex pelvic pain in three cohorts of women and to assess associations between demographic and gynecological characteristics and the severity of the condition. Material and methods In our cross‐sectional study, we collected self‐reported data from patients referred to gynecological outpatient clinics, members of vulvodynia or endometriosis patient associations, and healthy volunteers. The 397 participants (47% response rate) completed an online survey about their demographic and gynecological characteristics and symptoms related to complex pelvic pain, including the Norwegian ACPPS. Score means on questionnaires, with standard deviations and 95% confidence intervals, were recorded. We used Pearson's chi‐square test, Analysis of variance and multivariable linear regression were used to assess associations of demographic and gynecological characteristics with ACPPS scores. Results Members of the patient associations had significantly higher self‐reported symptom burden than patients and volunteers. Symptom burden was lower among older and postmenopausal women, and unemployed women scored higher than employed ones. Especially high scores on the ACPPS were found among women with complaints of chronic pelvic pain, at least moderate pelvic pain intensity, and/or chronic vulvar pain. Women who had experienced sexual assault and/or reported low sexual function also reported high scores. In multivariable regression, fibromyalgia, low mental health and past sexual assault were found to be associated with high scores on the ACPPS. Conclusion Many women in our study reported complex pelvic pain, and overlap with other pain‐related conditions, low mental health and past sexual assault was associated with high symptom burden. Those findings support taking a biopsychosocial approach to treating women who present with such complaints.